P104 A case of allergic enterocolitis to milk protein in a down baby. (6th June 2017) - Chiossi, L; Marinari, A; Catucci, A; Taurino, L; Calabrese, C; Liberatore, P; Lotti, F; Cringoli, S; Lanzano, A; Coretti, A; Magaldi, R; Pettoello-Mantovani, M
Abstract : Anna, a term baby born by Caesarean section, firstborn, Apgar 8/9, born SGA 2.630 g weight; performed in karyotype of Down syndrome suspected 'free trisomy of chromosome 21', echocardiography and abdominal ultrasound normal, ABR REFER, discharged in 8th day of life with diet of mother's milk integrated with zero infant formula. Hospitalisation at one month of life due to serious clinical conditions (dehydration, hypovolemic shock, metabolic acidosis, PCR 67, 4 mg/L, PCT 4, 45 ng/ml, leukocytosis 63870/microL, weight 2447 g); negative blood, liquor, urine and stool cultures; Chest and Abdomen X-ray showed meteoric distension of the intestinal loops. She began antibiotic (Ampicillin+Sulbactam, Netilmicin, Ceftazidime) and immunoglobulin therapy with improvement and reduction of inflammatory markers; feeding with zero infant formula. After the fourth day of hospitalisation spontaneous emission of greenish bloody stools and then liquid stools, hypotonus, metabolic acidosis, bulbous abdomen, fever, increased inflammatory markers and leukocytosis occurred despite antibiotic therapy. New negatives cultures tested, negative parasitological faecal examination, positive faecal calprotectin (702.59 mg/kg); lymphocyte subpopulations and normal immunoglobulins. Anaemia with need of blood transfusion. Therapy replaced with Meropenem and Vancomycin and diet with hydrolyzed infant formula with slight improvements. The appearance of two similar to previous episodes in the following days suggested to treat with antibiotics and immunoglobulins. After gastroenterological consulting, in allergic enterocolitis to milk protein suspect, it replaced diet with hydrolyzed infant formula with amino acids. The following days progressive clinical improvement noted, weight increase, normal inflammatory markers, good conditions and subsequently discharge. Three weeks later, during medical check-up, she appeared in good clinical condition, increase in weight of 650 g